Perancangan Multiple Tray Aerator Sebagai Pretreatment Proses Reverse Osmosis untuk Pengolahan Air Baku Sungai Itik Kabupaten Kubu Raya - Abshar, Khairul; Purnaini, Rizki; Danial, Mochammad Meddy (Jurnal Teknologi Lingkungan Lahan Basah, 2023)
The Itik River is used by the community as a source of clean water for daily needs such as bathing and washing, the characteristics of the Itik River water do not meet the requirements for water based on PERMENKES No. 32 of 2017. The characteristics of the Itik River water have the parameter Iron (Fe) 1.15 mg/ l which exceeds the quality standard. The design of multiple tray aerators is expected to reduce iron in the Itik River raw water to meet water standard requirements before entering the reverse osmosis process. The method used to reduce iron (Fe) in water is aeration with multiple tray aerators. Initial sample concentration of iron (Fe) 3.22 mg/l, TDS 844 mg/L, pH 7.1 and DO 6.0. The design of multiple tray aerators consists of design calculations, design making, preparation of tools and materials, and the tool building process. The multiple tray aerator is designed to have a capacity of 1000 l/day with 5 tiers of trays. Multiple tray aerator dimensions: length = 1.5 m, width = 1.3 m, height = 4.3 m. The distance between each tray is 60 cm, the number of holes per tray is 1,512, the hole diameter is 4 mm, and the distance between holes is 2 cm. The results of water treatment obtained a decrease in concentration (Fe) of 94.44%, TDS became 838 mg/L, pH became 7.9 and DO 6.9 mg/l. The total RAB needed to build multiple tray aerators made of iron is Rp. 4,380,000.